Evaluating Optical Proxies of Particulate Organic Carbon across the Surface Atlantic Ocean - Rasse, Rafael; Dall'Olmo, Giorgio; Graff, Jason; Westberry, Toby K.; van Dongen-Vogels, Virginie; Behrenfeld, Michael J. (Frontiers in Marine Science, 2017)
Empirical relationships between particulate organic carbon (POC) and inherent optical properties (IOPs) are required for estimating POC from ocean-colour remote sensing and autonomous platforms. The main relationships studied are those between POC and particulate attenuation (cp) and backscattering (bbp) coefficients. The parameters of these relationships can however differ considerably due to differences in the methodologies applied for measuring IOPs and POC as well as variations in particle characteristics. Therefore it is important to assess existing relationships and explore new optical proxies of POC. In this study, we evaluated empirical relationships between surface POC and IOPs (cp, bbp and the particulate absorption coefficient, ap) using an extensive dataset collected during two Atlantic Meridional Transect (AMT 19 and 22) cruises spanning a wide range of oceanographic regimes. IOPs and POC were measured during the two cruises using consistent methodologies. To independently assess the accuracy of the POC-IOPs relationships, we predicted surface POC for AMT-22 using relationships developed based on independent data from AMT-19. We found typical biases in predicting POC ranging between 2-3%, 4-9%, and 6-13% for cp, bbp and ap, respectively, and typical random uncertainties of 20-30%. We conclude that 1) accurate POC-cp and POC-bbp relationships were obtained due to the consistent methodologies used to estimate POC and IOPs and 2) ap could be considered as an alternative optical proxy for POC in open-ocean waters, only if all physiological variability in the POC:chl ratio could be modeled and used to correct ap.